Fiscal Rules and the Scope for Risk Sharing - Iain Begg (Intereconomics, 2017)
The trade-off between risk reduction and risk sharing has been at the heart of debates concerning EU economic governance over the last five years, but there are few signs as yet of a solution being reached.
Keywords: 330